Alpha‐Lipoic Acid Restored Antioxidant Capacity of Megalobrama amblycephala Inhibited by Ammonia - Xinyu Xiong; Han Zhang; Hui Xiao; Qian Wang; Jinzhu Cen; Mengyang Dai; Canli Wang; Xiangyang Yuan (Journal of Fish Diseases, 2026)
This study assessed recovery of alpha‐lipoic acid (α‐LA) on antioxidant capacity of blunt snout bream ( Megalobrama amblycephala ) juveniles after ammonia stress. Around 270 healthy juveniles (13.7 ± 1.6 g) were separated into three groups and exposed to ammonium chloride solutions at 0 (G1), 5.45 (G2), and 10.89 mg/L (G3). Ammonia stress lasted for 72 h, then all fish were transferred to aerated tap water for the recovery experiment. Each group was further divided into three subgroups, which were fed with three diets with 0, 0.6, and 1.2 g/kg α‐LA, respectively. The recovery experiment also lasted for 72 h. Gill and liver were collected after ammonia stress and recovery for the enzyme activities, histology, gene expression and correlation analysis. The results showed that total antioxidant capacity (T‐AOC), superoxide dismutase (SOD), and catalase (CAT) activities of liver and gill in G2 and G3 were significantly lower than G1 ( p p p